2000
DOI: 10.1161/01.str.31.5.1136
|View full text |Cite
|
Sign up to set email alerts
|

Regional Myocardial Perfusion After Experimental Subarachnoid Hemorrhage

Abstract: Background and Purpose-The pathophysiology of cardiac injury after subarachnoid hemorrhage (SAH) remains controversial. Data from animal models suggest that catecholamine-mediated injury is the most likely cause of cardiac injury after SAH. However, researchers also have proposed myocardial ischemia to be the underlying cause, as a result of coronary artery disease, coronary artery spasm, or hypertension and tachycardia. To test the hypothesis that SAH-induced cardiac injury occurs in the absence of myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 30 publications
1
44
0
1
Order By: Relevance
“…Animal models suggest that catecholamine-mediated injury is the cause of ECG abnormalities after a SAH. In a canine SAH model [43], regional cardiac wall motion abnormalities detected by echocardiography were found in 8 of 9 SAH dogs vs. 1 of 5 controls, and ischemic-like ECG changes were observed in 5 of 8 SAH dogs vs. 1 of 5 controls, but not all of these changes were accompanied by myocardial hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models suggest that catecholamine-mediated injury is the cause of ECG abnormalities after a SAH. In a canine SAH model [43], regional cardiac wall motion abnormalities detected by echocardiography were found in 8 of 9 SAH dogs vs. 1 of 5 controls, and ischemic-like ECG changes were observed in 5 of 8 SAH dogs vs. 1 of 5 controls, but not all of these changes were accompanied by myocardial hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the etiology of cardiac injury in the majority of patients with SAH is due to reversible left ventricular systolic dysfunction rather than underlying obstructive coronary artery disease [7]. The mechanism of cardiac injury is thought to be secondary to a sudden surge in catecholamine levels [8][9][10] resulting in functional myocardial stunning [7] and focal contraction band necrosis. Therefore, neurocardiac injury is likely directly responsible for left ventricular dysfunction and elevated cardiac biomarkers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Normal cardiac perfusion is also demonstrated by myocardial contrast echocardiography in neurogenic-stunned myocardium initial MRI brain FLAIR demonstrates increased T2 signal in the bilateral frontal lobes, thalamus, and cerebellum (arrows). Bottom panel: repeat MRI brain FLAIR at 1 month confirms complete resolution of the previously seen T2 signal hyperintensities patients [6][7][8]. The more accepted theory explaining neurogenic-stunned myocardium is called the ''catecholamine hypothesis.''…”
Section: Discussionmentioning
confidence: 87%